2017
DOI: 10.1002/hyp.11235
|View full text |Cite
|
Sign up to set email alerts
|

Variability of dissolved organic carbon in precipitation during storms at the Shale Hills Critical Zone Observatory

Abstract: Organic compounds are removed from the atmosphere and deposited to the Earth's surface via precipitation. In this study, we quantified variations of dissolved organic carbon (DOC) in precipitation during storm events at the Shale Hills Critical Zone Observatory, a forested watershed in central Pennsylvania (USA). Precipitation samples were collected consecutively throughout the storm during 13 events, which spanned a range of seasons and synoptic meteorological conditions, including a hurricane. Further, we ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 82 publications
0
4
0
2
Order By: Relevance
“…Changes in solute concentrations during precipitation events have been observed, but the causes can be difficult to pinpoint because the dissolved constituents can be incorporated by within‐cloud or below‐cloud scavenging or advection (Beverland & Crowther, 1992). There is not a consistent pattern of DOC concentration over time in storm events, but the middle of the storm tends to have the lowest concentrations (Iavorivska et al., 2017). The DOC concentration can reflect multiple possible source areas containing gases and aerosols that can be incorporated in precipitation as well as changes in the rate of precipitation over time.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in solute concentrations during precipitation events have been observed, but the causes can be difficult to pinpoint because the dissolved constituents can be incorporated by within‐cloud or below‐cloud scavenging or advection (Beverland & Crowther, 1992). There is not a consistent pattern of DOC concentration over time in storm events, but the middle of the storm tends to have the lowest concentrations (Iavorivska et al., 2017). The DOC concentration can reflect multiple possible source areas containing gases and aerosols that can be incorporated in precipitation as well as changes in the rate of precipitation over time.…”
Section: Discussionmentioning
confidence: 99%
“…Considerando-se que o COD de origem atmosférica foi liberado/emitido de outros lugares, áreas que se localizem próximas a grandes centros urbanos ou parques industriais podem receber uma entrada de COD via precipitação maior do que áreas mais distantes destes centros, embora a força da circulação atmosférica possa transportar tais moléculas até longas distâncias (Zhang et al, 2017;Iavorivska et al, 2017). A tabela 1 apresenta valores de concentração de COD na precipitação inicial observados por diferentes pesquisadores em variados ambientes.…”
Section: Precipitação Inicial: Deposição úMidaunclassified
“…Um estudo detalhado sobre as variações de concentração de COD na precipitação ao longo dos eventos de chuva foi conduzido por Iavorivska et al (2017). Estes autores indicaram a tendência de redução das concentrações com o progresso dos eventos.…”
Section: Precipitação Inicial: Deposição úMidaunclassified
“…Apparently, stream DOM can be significantly influenced by allochthonous loading and autochthonous products from riparian zones and uplands(Williams et al, 2010;Wilson & Xenopoulos, 2009). The observed flow paths, including surface runoff, interflows, fracture flows, groundwater and even precipitation, have a significant influence on DOM quantity and quality in hydrological processes; variations in the preferential flows of stream would change DOM sources under different hydrological conditions(Iavorivska et al, 2017;Xian et al, 2018). However, due to the very thick layer of loess covering the study area, the groundwater table was measured at approximately 60-80 m and was found to supply little discharge for stream flows (Groundwater Research Group of the Loess Plateau Comprehensive Scientific Expedition Team, Chinese Academy ofSciences, 1990).…”
mentioning
confidence: 99%